Mitochondrial and Redox Modifications in Huntington Disease Induced Pluripotent Stem Cells Rescued by CRISPR/Cas9 CAGs Targeting - Lopes, Carla; Tang, Yang; Anjo, Sandra I.; Manadas, Bruno; Onofre, Isabel; de Almeida, Luís P.; Daley, George Q.; Schlaeger, Thorsten M.; Rego, Ana Cristina Carvalho (Frontiers in Cell and Developmental Biology, 2020)
Mitochondrial deregulation has gained increasing support as a pathological mechanism in Huntington's disease (HD), a genetic-based neurodegenerative disorder caused by CAG expansion in the HTT gene. In this study we thoroughly investigated mitochondrial-based mechanisms in HD patient-derived iPSC (HD-iPSC) and differentiated neural stem cells (NSC) versus control cells, as well as in cells subjected to CRISPR/Cas9-CAG repeat deletion. We analysed mitochondrial morphology, function and biogenesis, linked to exosomal release of mitochondrial components, glycolytic flux, ATP generation and cellular redox status. Mitochondria in HD cells exhibited round shape and fragmented morphology. Functionally, HD-iPSC and HD-NSC displayed lower mitochondrial respiration, exosomal release of cytochrome c, decreased ATP/ADP, reduced PGC-1alpha and complex III subunit expression and activity, and were highly dependent on glycolysis, supported by pyruvate dehydrogenase (PDH) inactivation. HD-iPSC and HD-NSC mitochondria showed ATP synthase reversal and increased calcium retention. Enhanced mitochondrial reactive oxygen species (ROS) were also observed in HD-iPSC and HD-NSC, along with decreased UCP2 mRNA levels. CRISPR/Cas9-CAG repeat deletion in HD-iPSC and derived HD-NSC ameliorated mitochondrial phenotypes. Data attests for intricate metabolic and mitochondrial dysfunction linked to transcriptional deregulation as early events in HD pathogenesis, which are alleviated following CAG deletion.